Vitamin D status, vitamin D receptor, CYP2R1, and CYP24A1 profiles in children - Iriani, Anggraini; Rachman, Andhika; Fatina, Marsya Kaila; Gemilang, Rizka Kurnia; Trisnandi, Andi; Muskananfola, Fiona Valerie; Nugraha, Media Fitri Isma (Frontiers in Nutrition, 2024)
Introduction: Vitamin D plays a major role in the musculoskeletal and immune system. Understanding the comprehensive mechanism of vitamin D receptors and the enzyme of vitamin D induction (CYP2R1) and inhibition (CYP24A1) in its metabolism is interesting. This study aims to understand vitamin D metabolism in Indonesian pediatrics, specifically in Jakarta, which has abundant sun exposure. Vitamin D deficiency is prevalent in both tropical and nontropical countries. Several cytochromes, including CYP2R1 and CYP24A1, mediate vitamin D metabolism. In order to function, vitamin D needs to bind to vitamin D receptors.A cross-sectional study with comparative, and correlative, and multivariate analysis on vitamin D, vitamin D receptor, CYP2R1, and CYP24A1 levels was conducted on 46 children with no known morbidity.Result: Subjects were mostly male (52.2%), age group of 2-6 years (34.8%), and had sufficient vitamin D status (43.5%, median 27.55 ng/ml). Age was found to have a negative correlation with vitamin D levels (p<0.001; r=-0.625) and CYP2R1 (p=0.035; r=-0.311). Significant positive associations were found between CYP24A1 and CYP2R1 (p=0.046; r=0.296). Participants aged 0-2 are more likely to have a higher level of vitamin D status compared to those aged >2 years (OR 42.092, 390.914], p=0.001). VDR levels were significantly lower in insufficient vitamin D levels than in the sufficient group (p=0.018). VDR and vitamin D status had a positive relation (OR 7.023,], p=0.004).Vitamin D and CYP2R1 levels decrease with the increase in age. Vitamin D receptor level has an inline-level progression with vitamin D level. CYP2R1 and CYP24A1 suggest a directly proportional relationship. Vitamin D screening and supplementation in children older than 2 years old are suggested.